Pengaruh Bermain Wire Maze Terhadap Kontak Mata Anak Autis Spectrum Disorder di KB/TK Inklusi Srawung Bocah Yogyakarta: The Effect Of Playing Wire Maze on The Eye Contact Of Children With Autism Spectrum Disorder In Kb/Tk Inklusi Srawung Bocah Yogyakarta - Dwike Amalia; Dwi Putri Fatmawati (Universitas Ngudi Waluyo, 2023)
The effect of playing wire maze on the eye contact of children with autism spectrum disorder in KB/TK Srawung Bocah Inklusi, reports on children's learning outcomes and observations of class teachers concluded that there were student problems in the form of a lack of ability to make eye contact in children so that it affected children's communication activities in learning activities. The aim of the study was to determine the effect of playing wire maze on eye contact in children with autism spectrum disorder. The research was conducted by calculating the frequency of eye contact in ASD children. In this study the researcher used observation and documentation as data collecting technique, with a quantitative approach and the type of experimental research with the Single Subject Research (SSR) design. The results of data analysis found that there were differences in the results in each research phase, it was in the baseline phase which increased in the intervention phase. Based on these results it can be concluded that there is an effect from playing wire maze on the eye contact of ASD children Â ABSTRAK Pengaruh bermain wire maze terhadap kontak mata anak autism spectrum disorder di KB/TK Inklusi Srawung Bocah, laporan hasil belajar anak dan pengamatan guru kelas menyatakan adanya permasalahan siswa berupa kurangnya kemampuan kontak mata anak sehingga mempengaruhi kegiatan anak berkomunikasi dalam kegiatan pembelajaran. Penelitian bertujuan untuk mengetahui pengaruh bermain wire maze terhadap kontak mata anak autism spectrum disorder, penelitian dilakukan dengan menghitung frekuensi munculnya kontak mata pada anak ASD. Pengumpulan data dalam penelitian ini yaitu observasi dan dokumentasi, dengan pendekatan kuantitatif dan jenis penelitian eksperimen dengan desain Single Subject Research (SSR). Hasil Analisis data didapatkan bahwa adanya perbedaan hasil dalam setiap fase penelitian, yaitu pada fase baseline yang meningkat di fase intervensi. Berdasarkan hasil tersebut dapat disimpulkan bahwa terdapat pengaruh bermain wire maze terhadap kontak mata anak ASD.